Analysis of adverse drug reactions in a tertiary care teaching hospital in Southern India - Sai, Nagaraja Prasad (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Medication use has been there since time immemorial. Also, it was well known that all medications carry risk of adverse drug events. Hence regular and periodic monitoring of medications for adverse events has assumed importance. With this background pharmacovigilance has an important role to play in monitoring of adverse events to medications. Hence the present study was undertaken to analyze the pattern of adverse events reported to a tertiary care teaching hospital in Southern India (Shivamogga Institute of Medical Sciences (SIMS), Shimoga). Methods: This study is a retrospective observational study of 150 adverse drug events reported at McGann teaching hospital, SIMS, Shimoga. The adverse events reported were analyzed for their age and gender distribution, drugs causing ADRs, organ systems affected, causality, type, severity and preventability of ADRs. Results: Patients in age groups of 21-40 were most commonly affected by ADRs with a slight increase in male population affected. Cutaneous ADRs were most common and beta lactam antibiotics were most common drug group implicated in causing these ADRs. Probable/likely category most common WHO-UMC causality category, with type A ADRs being most common. Majority of ADRs were of moderate severity and nearly 86% of ADRs were of not preventable category. Conclusions: Antimicrobials were most commonly involved in causation of ADRs with cutaneous ADRs being most common. Most of ADR were not preventable category, majority of ADRs were of moderate severity and causality grading was probable/likely category.